2008
DOI: 10.1007/s10601-007-9037-5
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of Locally Defined Submodular Functions by Optimal Soft Arc Consistency

Abstract: Submodular function minimization is a polynomially solvable combinatorial problem. Unfortunately the best known general-purpose algorithms have highorder polynomial time complexity. In many applications the objective function is locally defined in that it is the sum of cost functions (also known as soft or valued constraints) whose arities are bounded by a constant. We prove that every valued constraint satisfaction problem with submodular cost functions has an equivalent instance on the same constraint scopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
(86 reference statements)
0
23
0
Order By: Relevance
“…An important and well-studied subproblem of SFM is the minimisation of submodular functions of bounded arity (SFM b ), also known as locally-defined submodular functions [73], or submodular functions with succinct representation [114]. In this scenario the submodular function to be minimised is defined by the sum of a collection of functions which each depend only on a bounded number of variables.…”
Section: Definition 111 (Submodularity On Sets)mentioning
confidence: 99%
See 2 more Smart Citations
“…An important and well-studied subproblem of SFM is the minimisation of submodular functions of bounded arity (SFM b ), also known as locally-defined submodular functions [73], or submodular functions with succinct representation [114]. In this scenario the submodular function to be minimised is defined by the sum of a collection of functions which each depend only on a bounded number of variables.…”
Section: Definition 111 (Submodularity On Sets)mentioning
confidence: 99%
“…7) [188]. An alternative approach to solving VCSP instances with submodular constraints, based on linear programming, has been proposed in [73]. Recently, Thapper and Živný have shown that linear programming can be used to solve VCSPs with submodular constraints with respect to any lattice.…”
Section: Definition 111 (Submodularity On Sets)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in the literature that for a submodular clique potential function, there are algorithms to produce a globally optimal solution in polynomial time [5,14] for two class problems. This section analyzes the proposed clique function to identify what properties make it submodular and therefore can be solved efficiently and accurately with existing algorithms.…”
Section: Submodularity and Tractabilitymentioning
confidence: 99%
“…Problems with nonlinear g c (·) can be solved using a linear programming (LP) formulation suggested in [5,14]. See [11,22] and references therein to learn more about various inference algorithms available in the literature.…”
Section: General Case: Nonlinear G C (·)mentioning
confidence: 99%